ANALISIS TINGKAT PELAYANAN PEJALAN KAKI PADA TROTOAR BERDASARKAN PENGAMATAN VISUAL - , AHMAD BASTOMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pedestrians is one components of road users which they are very vulnerable and weak. Transportation facilities that good standards should provide a separate space for the road users. A matter of fact, the space for pedestrians must be provided, in order to avoid a pedestrian from vehicle collision. Good pedestrian facilities are able to create an atmosphere that is comfortable, safe and enjoyable for its users. Sidewalks should also have its own standard to serve its users. This makes the pedestrian level of service to be one case to be considered when designing the sidewalk. Pedestrian level of service (LOS pedestrian) should be able to serve all requirement of pedestrians. So when pedestrians walking in a space provided, pedestrians will feel comfortable, safe and interested. This research is related to the analysis method pedestrian level of service in terms of visuals by combining method of pedestrian LOS Gallin and method of pedestrian LOS Jaskiewicz. For the steps of research, they are: analyzing the factors that influence the pedestrian LOS Visual field. Then devise new standards and assessment system in pedestrian LOS Visual method. After that, do a case study in the field by applying the method of pedestrian LOS Visual already made and compare the results with the method of pedestrian LOS Gallin. Lastly, analyze and compare the results of the case study with a method of pedestrian LOS Visual and pedestrian LOS Gallin. Discussion of this result research concluded that the pedestrian LOS Visual methods are designed to have almost the same accuracy with the method of pedestrian LOS Gallin although the factors and its systems are different. In addition, the application of pedestrian LOS Visual methods at the time of the case study has several advantages over than the pedestrian LOS Gallin. They are: the results of the analysis in terms of visual factors are more detail, the time required to analyze is shorter and efficient, easy to implement and more effective to do and very suitable to be applied for the analysis of sidewalks in Indonesia, but did not rule out also to be applied in other countries.